Square Duct Cleaning Machine Using a Multistage Planetary Gear Mechanism for Removing Grease - Yosuke Momma; Takehiro Hitomi; Fumio Ito; Taro Nakamura (IEEE Access)
This study proposes a cleaning machine using a multistage planetary gear mechanism to remove accumulated grease from kitchen ducts with various geometries, including circular and square configurations. The contributions of this study encompass the design of the cleaning machine, that can scrub off grease accumulated at the four corners and near the central regions of the inner wall of square ducts at once—a task that has been difficult in the past. Furthermore, velocity simulations estimated the relative velocity of the brushes to the duct wall. Additionally, the results of the grease cleaning experiment conducted using the proposed machine were discussed. The aim was to clean accumulated grease within ducts using a single robot to prevent duct fires. It is difficult for conventional duct cleaning robots to clean grease because they do not consider the distinct properties inherent to grease, characterized by its elevated viscosity and tenacious adhesion. This study described the design and experiments of the cleaning machine, which enabled the machine to scrub the entire inner wall of a duct at a relative velocity of the brushes of 60 mm/s or higher, required to scrub off grease from the duct. The cleaning rate of the grease by the proposed machine was up to 80 % which is 2.3 times higher than in a previous study, and the proposed machine is expected to remove most of the grease accumulated in ducts. The results are expected to expand the cleaning area in cleaning the inner walls of square ducts.